Berberis aristata/Silybum marianum fixed combination on lipid profile and insulin secretion in dyslipidemic patients. (November 2013) - Derosa, Giuseppe; Bonaventura, Aldo; Bianchi, Lucio; Romano, Davide; D'Angelo, Angela; Fogari, Elena; Maffioli, Pamela
<x xml:space="preserve">Abstract</x> Background: Relatively large number of dietary supplements and nutraceuticals have been studied for their supposed or demonstrated ability to reduce cholesterolemia in humans. Objectives: The aim of this study was to evaluate the efficacy as antihypercholesterolemic and insulin-sensitizing agent of a combination of Berberis aristata/Silybum marianum extract (Berberol®) in a sample of dyslipidemic patients. A total of 102 dyslipidemic subjects were enrolled. After a 6 months run-in period of diet and physical activity, the patients were randomized to placebo or Berberis aristata/Silybum marianum extract 588 mg/105 mg, twice a day for 3 months. Berberis aristata/Silybum marianum and placebo were then interrupted for 2 months (washout period), and then restarted for further 3 months. Anthropometric and metabolic parameters were assessed; moreover, all patients underwent a glucagon stimulation test. Results: Berberis aristata/Silybum marianum reduced total cholesterol, triglycerides and low-density lipoprotein cholesterol and increased high-density lipoprotein cholesterol after 3 months from randomization and compared to placebo group. When Berberis aristata/Silybum marianum was interrupted, lipid profile worsened, and it improved again when nutraceutical combination was reintroduced. During the glucagon stimulation test, a higher increase of C-peptide levels and a lower increase in glycemia after the test with Berberis aristata/Silybum marianum compared to placebo, to baseline and to randomization were recorded. No patients had serious adverse events in both groups. Conclusion: Berberis aristata/Silybum marianum is effective and safe in improving lipid profile and insulin secretion in euglycemic dyslipidemic patients.